Effect of Carbonization Temperature on Pore Formation and Adsorption Ability of Coconut Shell Activated Carbon with KOH Activator - Arinda Yukashima Putri Prahesti; Sheilla Rully Anggita; Hamdan Hadi Kusuma (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2025)
Activated carbon derived from coconut shells has great potential as an adsorbent for water purifi-cation due to its high porosity. This study investigates the effect of carbonization temperature on pore formation and adsorption capacity of coconut shell activated carbon. Carbonization was conducted at temperatures rang-ing from 500◦C to 700◦C for 2 hours, followed by chemical activation using 3M KOH solution. The activated carbon was then filtered, washed until neutral pH (± 7), and dried. Characterization was carried out using the BET method to analyze surface area and pore volume, while adsorption capacity was determined using a UV-Vis spectrophotometer with methylene blue as the adsorbate. The results show that increasing the car-bonization temperature enhances pore development, as indicated by higher surface area and pore volume. The highest surface area and pore volume were obtained at 700◦C, reaching 426.692 m2/g and 2.414 cc/g, respec-tively. Correspondingly, the highest adsorption capacity was also observed at 700◦C, with a value of 3957.15 mg/g. These findings suggest that carbonization temperature plays a critical role in optimizing the physical characteristics and adsorption performance of coconut shell-based activated carbon.